Effect of gamma radiation on the changes of biochemical, morphologicial and technological characteristics for potato tubers during storage - Nassef, Ashga E.; El-Korayf,Amal N. (2003)
The investigation aimed to study the influence on gamma irradiation of postharvest potato tubers for extending their shelf-life for more than six months. Two cultivars were used i.e. Diamont and Spunta cvs., in this investigation. using two different doses of gamma irradiation i.e. 50 and 150 Gry, in addition to a control (unirradiated tubers). Thus, 18 treatments were carried out with their replications for measuring physical, physiological and microbiological characters. Percentage of sprouts rot tubers, total count of bacteria, yeast and fungi counts were determined. Moreover, chemical constituents were determined, induding moisture, dry matter percentage, total soluble sugars, ascorbic acid (vitamin C), amino acids and nucleic acids (RNA and DNA) content.
Includes reference.
Summary in Arabic.
1
Keywords: Potatoes -- Storage -- Research; Gamma rays -- Physiological effect